Mediasi Profitabilitas Pada Perputaran Aset dan Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar di BEI Tahun 2013-2017) - Azizi, Enji; Akhmadi, Akhmadi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2019)
This study aims to examine the effect of aset turnover ratio which is proxied by Total Assets Turnover (TATO) on the value of the company proxied by Price to Book Value (PBV) through profitability proxied by Return On Assets (ROA) as a mediating variable. The research was conducted at manufacturing company of consumer goods industry sector in 2013-2017 with the number of samples taken as many as 31 companies. Research data in the analysis using path analysis with the help of SPSS version 19.00. The results of hypothesis testing obtained by TATO have no effect on PBV, TATO has a positive and significant effect on ROA, ROA has a positive and significant effect on PBV. The results of the mediation test concluded that the indirect influence of TATO on PBV through ROA was greater than the direct influence of TATO on PBV which proved that ROA was able to mediate TATO's relationship to PBV